ITGA4 Contributes to 5-Fluorouracil Resistance by Up-Regulating PI3K/AKT Signaling: Evidence from Network Pharmacology, Molecular Docking and Experimental Verification - Yan S; Hu X; Wu Y; Ye W; Zhu Y; He Y; Zhan F; Wu W; Ma Z (Drug Design, Development and Therapy)
Sicheng Yan,1 Xiaomeng Hu,1 Yan Wu,1 Wangfang Ye,1 Yuehong Zhu,1 Yuxuan He,1 Fuyuan Zhan,1,2 Wei Wu,3 Zhihong Ma1,2 1Huzhou Key Laboratory of Molecular Medicine, Huzhou Central Hospital, Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, Huzhou, Zhejiang, 313000, People’s Republic of China; 2School of Basic Medicine College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310000, People’s Republic of China; 3Key Laboratory of Multiomics Research and Clinical Transformation of Digestive Cancer of Huzhou, Huzhou Central Hospital, Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, Huzhou, Zhejiang, 313000, People’s Republic of ChinaCorrespondence: Wei Wu, Key Laboratory of Multiomics Research and Clinical Transformation of Digestive Cancer of Huzhou, Huzhou Central Hospital, Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, Huzhou, Zhejiang, 313000, People’s Republic of China, Tel +86 05722023301, Email hchwuwei2018@126.com Zhihong Ma, Huzhou Key Laboratory of Molecular Medicine, Huzhou Central Hospital, Fifth School of Clinical Medicine of Zhejiang Chinese Medical University, Huzhou, Zhejiang, 313000, People’s Republic of China, Tel +86-18757295186, Email mazhihong@hzhospital.comObjective: 5-Fluorouracil (5-FU) is a mainstream drug used in chemotherapy and chemoradiotherapy regimens for the clinical treatment of malignancies, such as gastric cancer (GC), colorectal cancer, and breast cancer. However, the molecular mechanism of action of 5-FU in GC has not yet been studied using a network pharmacology approach.Methods: The mechanism of action of 5-FU in GC was determined using a network pharmacology technique, and our findings were confirmed by various computational approaches and experimental tests using the GeneCards database, ChEMBL database, STRING database, molecular docking, molecular dynamics simulation, DAVID, GEPIA, Kaplan‒Meier Plotter, CCK-8 assays, colony formation experiments, cell proliferative assay, apoptosis assays, wound-healing assays, Real-time PCR and Western blot tests.Results: A total of 21 shared and 13 potential targets were identified using PPI network analysis. Kyoto Encyclopaedia of Genes and Genomes (KEGG) enrichment analyses indicated that the PI3K/AKT signaling pathway may be a significant pathway. Combined with molecular docking and database verification, F10, NR3C1, DHFR, CA2, BCHE, ACHE, and ITGA4 were identified as candidate core genes. Moreover, the experimental results illustrated that ITGA4 induces 5-FU resistance by up-regulating PI3K/AKT signaling.Conclusion: Network pharmacology is a feasible scientific research strategy for revealing the multitarget-multipathway role of 5-FU in the treatment of GC and provides ITGA4-based new ideas and therapeutic strategy to overcome 5-FU resistance for GC treatment.Keywords: 5-FU, gastric cancer, network pharmacology, molecular docking, ITGA4, PI3K/AKT pathway, resistance